Dinamika Relasi Manusia dengan Allah Menurut Thomas Merton - Kesuma, Petrus Tunjung (Jurnal Orientasi Baru, 2011)
Merton’s thought on Christian’s involvement in human issues is the result of hisstruggle in living spiritual life. At first, as a young monk he thought that in orderto meet God someone must break away from all sorts of problems that occur insociety. However, in subsequent developments, he discovered that when peoplewalked toward God through contemplation, where he had to detach his false selfand then discover his inner self, he will find that in his inner self a person is notonly in unity with God, but also with his fellowmen. Thus contemplation is a seaof love where person is in unity with God and his fellowman. Contemplation is adynamic experience of loving God animating a fraternal and peaceful life.